Effect of Blending Degree between Virgin and Aged Binder on Pavement Performance of Recycled Asphalt Mixture with High RAP Content - Ying Xu; Zhijing Chou; Yunze Li; Jie Ji; Shi-fa Xu (Advances in Materials Science and Engineering)
In this study, the influence of the blending degree between virgin and aged binder on the pavement performance of hot-mix recycled asphalt mixture (HMRAM) with high RAP content is analyzed. The aggregate gradation of AC-16 was selected. The RAP contents were 30, 40, and 50%. HMRAMs with different degrees of blending (DOBs) were prepared by changing the mixing temperature (150, 165, and 180°C) without the occurrence of excessive aging for asphalt binders. An improved Hirsch dynamic modulus prediction model was then used to quantitatively characterize the DOB of HMRAM. Finally, the high-temperature, low-temperature, moisture stability, and fatigue resistance performance of HMRAM were tested and the effect of the DOB between the virgin and aged asphalt binder on the pavement performance was analyzed. The results showed that the DOB between the virgin and aged asphalt binder cannot reach 100% at the three mixing temperatures for HMRAM with 30, 40, and 50% RAP contents, which is inconsistent with the assumption of complete blending in China’s specification. The dynamic stability of the mixture gradually decreases with the increased DOB for HMRAM with a high RAP content, while the moisture stability, low-temperature, and fatigue resistance performance are continuously improved. This means that with the increase in DOB in the stage of open to traffic, meeting high-temperature performance criteria at the design stage may become unsatisfactory for HMRAM. The moisture stability, low-temperature performance, and fatigue resistance performances of HMRAM measured at the design stage were reasonable and conservative. The change in DOB significantly affects the content and properties of total free binder in HMRAM, affecting pavement performance. The content and physical properties of the RAP aggregate also have a significant impact on pavement performance.